Sexual Dimorphism and Body Reconstruction of a Hornless Rhinocerotid, Plesiaceratherium gracile, From the Early Miocene of the Shanwang Basin, Shandong, China - Lu, Xiaokang; Deng, Tao; Zheng, Xiaoting; Li, Fuchang (Frontiers in Ecology and Evolution, 2020)
We investigated the sexual dimorphism and reconstructed the body of Plesiaceratherium gracile based on the numerous new specimens from the Early Miocene Shanwang Basin, China. The sexual dimorphism of P. gracile is reflected by the size of both the lower incisor i2 [length male/female (M/F) ratio = 2.69, width M/F = 1.63] and the upper incisor I1 (length M/F = 1.63). Other mensural variations reveal their ranges greatly overlapping on both genders, with a low M/F ratio; hence, they cannot be interpreted as sexual dimorphism. The large-sized body and the strong sexual difference of incisors suggest that P. gracile is polygynous and has a solitary lifestyle. When we reconstructed the body of P. gracile, we found that the head-body length is 2,796–3,117 mm, the shoulder height is 1,476–1,627 mm, and the body weight is about 1,198 kg. All skeletons have the ventral edge of the thorax at the level of the olecranon of the ulna. The spinous processes of the posterior thoracic vertebrae and the lumbar vertebrae are always vertical, the metatarso-femur ratio and the tibio-femur ratio are high, and the two joint angles between the scapula, the humerus, and the radius are 102°–143° and 115°–160°, respectively, indicating that P. gracile has a mediportal limb and a horse-gallop running type. Furthermore, the limb-segment comparisons of P. gracile and other rhinoceroses demonstrate that the proximal long bones, including the scapula, the humerus, and the femur, are important for the body height, regardless of whether their body is large or small-sized; the distal parts of the limb, including the metacarpus and the metatarsus, are sensitive to body mass changes.